Erbium-doped fiber amplifiers fundamentals and technology - Becker, P. C.
Erbium Fiber Amplifiers is a comprehensive introduction to the increasingly important topic of optical amplification. Written by three Bell Labs pioneers, the book stresses the importance of the interrelation of materials properties, optical properties, and systems aspects of optical fiber amplifiers. The floppy disk included with the book contains a PC based educational version of the sophisticated commercial amplifier simulation package OASIX (sold by the Specialty Fiber Group of Lucent Technologies). This powerful numerical simulation software allows one to simulate the performance of a real.